UAE work environment examining the influences of culture, gender and sector on managerial leadership competencies, job satisfaction and organizational commitment - Alhadhrami, Abdelrahman Zaid Mohamed Baqrain (Curtin University, 2013)
This research examined the influences of culture, sector, and gender on managerial leadership competencies in a multicultural and multinational work environment. Additionally, the research also attempted to understand the correlations between managerial-leadership competencies—job satisfaction; managerial-leadership competencies—organizational commitment; sector—managerial-leadership competencies; and sector—organizational commitment; in a multicultural, multinational UAE work environment. This study will contribute significantly to the development of UAE managers by highlighting the challenges and opportunities of the examined cultural group.